PENGARUH MODEL PJBL PEMBELAJARAN IPS TERHADAP PENGEMBANGAN KETERAMPILAN SOSIAL PADA SISWA KELAS III - Kamilah, Nayla Rosiana; Rana Gustian Nugraha; Cucun Sunaengsih (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to examine the effect of the Project-Based Learning (PJBL) model on the social skills of third-grade elementary school students. The problem discussed is the lack of students' social skills caused by conventional learning methods that do not actively involve them. This study uses a quantitative approach with a quasi-experimental research design of the Nonequivalent Control Group Design type. To obtain the sample, a saturated sampling method was used with two classes as research objects, namely the experimental class and the control class. Data collection tools included a social skills test and observation. From the analysis results, it is clear that the PJBL model has a significant effect on improving students' social skills, as indicated by the results of the paired sample t-test and a higher N-Gain value in the experimental class. Therefore, it can be concluded that the PJBL model is more effective than conventional learning methods in improving students' social skills. In research in the context of elementary education, instructors can use PJBL as a strategy that can foster a cooperative, engaging, and meaningful learning environment, as well as encourage the development of children's social character from a young age.